PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS XI MIA 1 SMA PGRI PEKANBARU - Wening Widyastari; Rini Dian Anggraini; Armis Armis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to improve the learning process and to improve mathematics achievement by applying problem based learning. The research is classroom action research that consist of two cycles and at the end of every cycle carried out mathematics achievement test . The subject of this research is students of class XI MIA 1 SMA PGRI Pekanbaru in the first semester academic years 2015/2016, there are 20 students in the class, consist of 9 boys and 11 girls who have heterogeneous academic ability. The research instrument consists of learning tools and data collection instruments consisting of observation sheet and mathematics learning result test. Data collection is done through observation and test of mathematics learning result. Based on the observation sheet of teacher and student activity showing the activity of teachers and students has been done well, seen some of the students began to participate actively and more responsible in learning process. Based on data analysis of mathematics learning outcomes, the percentage of students reaching KKM in knowledge competence increased from 35% in basic score to 55% in cycle I and 90% in cycle II. On attitude competence shows improvement, seen from percentage of student number reaching minimum completeness criteria at 35% at base score to 60% at cycle I and 90% in cycle II. The percentage of students reaching minimum completeness criteria in skill competence increased from 50% in base score to 80% in cycle I and 100% in cycle II. The results of this study concluded that the implementation of learning models based on problems can improve the learning process and improve student learning outcomes of grade XI MIA 1 SMA PGRI Pekanbaru in the even semester of the school year 2015/2016.Keywords: Mathematics learning outcome, Problem Based Learning, Class action research.